Multifaceted insights into the environmental adaptability of Arnebia guttata under drought stress - Liu, Qian; Liu, Haolin; Zhang, Min; Lv, Guoshuai; Zhao, Zeyuan; Chen, Xingyu; Wei, Xinxin; Zhang, Chunhong; Li, Minhui (Frontiers in Plant Science, 2024)
Introduction Global warming has led to increased environmental stresses on plants, notably drought. This affects plant distribution and species adaptability, with some medicinal plants showing enhanced drought tolerance and increased medicinal components. In this pioneering study, we delve into the intricate tapestry of Arnebia guttata, a medicinal plant renowned for its resilience in arid environments. By fusing a rich historical narrative with cutting-edge analytical methodologies, this research endeavors to demystify the plant’s intricate response to drought stress, illuminating its profound implications for medicinal valorization. Methods The methodology includes a comprehensive textual research and resource investigation of A. guttata, regionalization studies, field sample distribution analysis, transcriptome and metabolome profiling, rhizosphere soil microbiome analysis, and drought stress experiments. Advanced computational tools like ArcGIS, MaxEnt, and various bioinformatics software were utilized for data analysis and modeling. Results The study identified significant genetic variations among A. guttata samples from different regions, correlating with environmental factors, particularly precipitation during the warmest quarter (BIO18). Metabolomic analysis revealed marked differences in metabolite profiles, including shikonin content, which is crucial for the plant’s medicinal properties. Soil microbial community analysis showed variations that could impact plant metabolism and stress response. Drought stress experiments demonstrated A. guttata’s resilience and its ability to modulate metabolic pathways to enhance drought tolerance. Discussion The findings underscore the complex interplay between genetic makeup, environmental factors, and microbial communities in shaping A. guttata’s adaptability and medicinal value. The study provides insights into how drought stress influences the synthesis of active compounds and suggests that moderate stress could enhance the plant’s medicinal properties. Predictive modeling indicates future suitable growth areas for A. guttata, aiding in resource management and conservation efforts. The research contributes to the sustainable development of medicinal resources and offers strategies for improving the cultivation of A. guttata.